Serum Krebs von den Lungen-6: promising biomarker to differentiate CPFE from IPF: Serum KL-6: Discriminate CPFE from IPF - Demirdöğen, Ezgi; Görek Dilektaşlı, Aslı; Acet Öztürk, Nilüfer Aylin; Yeşilbursa, Dilek; Budak, Ferah; Öztürk, Alper; Coşkun, Funda; Ursavaş, Ahmet; Özkaya, Güven; Karadağ, Mehmet; Uzaslan, Esra (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2022)
Background Combined pulmonary fibrosis and emphysema (CPFE) has been recognised as a phenotype of pulmonary fibrosis. We aimed to compare serum surfactant protein-A (SP-A), surfactant protein-D (SP-D) and Krebs von den Lungen-6 (KL-6) levels, functional parameters, in CPFE and IPF (idiopathic pulmonary fibrosis) patients. Methods Patients diagnosed with ‘CPFE’ and ‘IPF’ were consecutively included in 6 months as two groups. The patients with connective tissue diseases are excluded. Results In this study, 47 patients (41 males, 6 females) with CPFE (n = 21) and IPF (n = 26) with a mean age of 70.12 ± 8.75 were evaluated. CPFE patients were older, had more intense smoking history, had lower DLCO/VA, lower FVC, and worse six-minute walking distance than the IPF group (p=0.005, p=0.027, p=0.02, p<0.001, p=0.001, respectively). Serum KL-6 levels were higher in CPFE group compared to IPF group [264.70 U/ml (228.90-786) vs 233.60 (101.8-425.4), p<0.001]. Serum KL-6 levels of 245.4 U/ml and higher have 81% sensitivity and 73% specificity for the discrimination of CPFE from IPF. Conclusions Our study has shown that serum KL-6 level is a promising biomarker to differentiate CPFE from IPF. In CPFE cases respiratory and functional parameters are worse than those of pure fibrosis cases.